G104 Inflation pressures and times during the resuscitation of prematurely born infants. (7th April 2014) - Bhat, PS; Murthy, V; Fox, G; Campbell, ME; Milner, AD; Greenough, A
Abstract : Aim: We have previously demonstrated that using the UK recommended inflation pressures (20/5 cmH2 O) for the first five inflations, expiratory tidal volumes (TVe) rarely exceeded the anatomical dead space (1) and end tidal carbon dioxide (CO2 ) levels were low (2). The inflation times, however, were usually much shorter than recommended. 1, 2 Our aim was to assess the effects of higher inflation pressures and longer inflation times. Methods: The responses to the first five inflations of infants of gestational age < 34 weeks resuscitated via a face mask were studied. Infants resuscitated using peak inflation pressures of 25 cmH2 O and short (<1.5 seconds) or long (>1.5 seconds) inflation times were matched by gestational age to infants resuscitated with peak pressures of 20 cmH2 O with short or long inflation times. A NM3 respiratory profile monitor was used to record the inflation pressures, flow, tidal volumes and end tidal CO2 levels. Active inflations were excluded from the analysis. Results: There were 12 infants in each of the four groups; the median gestational age of the infants was 31 (range 24–34) weeks. Infants resuscitated with short inflation times had higher expiratory tidal volumes when resuscitated at 25/5 cmH2 O compared to 20/5 cmH2 O (0.12 (range 0.10–6.8) mls/kg versus 3.21 (range 0.16 –12.20) mls/kg respectively), p= <0.001 and higher ETCO levels (2.05 (range 0.2–35.6) mm Hg versus 8.30 (range 0.3 –61) mm Hg respectively), p = 0.030. Infants resuscitated with long inflation times had higher expiratory tidal volumes when resuscitated at 25/5 cmH2 O compared to 20/5 cmH2 O (2.06 (range 0.18–13.2) mls/kg versus 1.94 (range 0.01–8.4) mls/kg respectively), p = 0.011, but similar ETCO levels. Conclusion: Increasing inflation pressures from 20/5 to 25/5 cmH2 O improved tidal volumes regardless of the inflation time used. References: Murthy V, Dattani N, Peacock JL, Fox GF, Campbell ME, Milner AD, Greenough A. The first five inflations during resuscitation of prematurely born infants. Arch Dis Child Fetal Neonatal Ed 2012 97: F249-F253 Murthy V, O'Rourke–Potocki A, Dattani N, Fox GF, Campbell ME, Milner AD, Greenough A. End tidal carbon dioxide levels during the resuscitation of prematurely born infants. Early Hum Dev 2012 Oct; 88(10):783-7.